Estimación probabilística de la amenaza de inundación de la cuenca alta de río Chicamocha en el municipio de Paipa-Boyacá (2021)
In recent years, floods have increased considerably around the world, leaving societies vulnerable to the destructive forces of nature. Colombia, not being the exception, has experienced catastrophic and costly floods in different departments, becoming the most relevant and costly natural hazard. For this reason, it is of great relevance for the country to generate mitigation strategies and early warning systems.